Study protocol for a pilot randomised controlled trial evaluating the effectiveness of oral trehalose on inflammatory factors, oxidative stress, nutritional and clinical status in traumatic head injury patients receiving enteral nutrition. Issue 9 (19th September 2022) - Ghorbani Dehbalaei, Moazzameh; Sahebkar, Amirhossein; Safarian, Mohammad; Khadem-Rezaiyan, Majid; Rezaee, Hamid; Naeini, Fatemeh; Norouzy, Abdolreza
Abstract : Introduction: In traumatic brain injury (TBI) patients, inflammatory processes and oxidative stress have been linked to the development of neurodegenerative diseases, disability, increased rate of muscle catabolism, malnutrition, hospital stay and mortality. Previous in vitro and in vivo studies have shown that trehalose can decrease inflammatory and oxidative factors. Therefore, the present study was designed to evaluate the effect of oral trehalose consumption on this marker in critically ill TBI patients at intensive care unit (ICU). Methods and analysis: This study is a pilot randomised, prospective and double-blind clinical trial. The study sample size is of 20 (10 patients in each group) TBI patients aged 18–65 years at ICU. Randomisation is performed by permuted block randomisation method. The allocation ratio is 1:1. An intervention group will receive 30 g of trehalose instead, as a part of the carbohydrate of daily bolus enteral feeding and the control group will receive standard isocaloric hospital bolus enteral feeding for 12 days. The inflammatory factors (C reactive protein, interleukin 6) and oxidative stress markers (glutathione, malondialdehyde, superoxide dismutase, pro-oxidant–antioxidant balance, total antioxidant capacity) will be measured at the baseline, at the 6th day, and at the end of the study (12th day). Sequential Organ Failure Assessment, Acute Physiology and Chronic Health Evaluation II, Nutrition Risk in the Critically ill scores, 28-day mortality, anthropometric assessments and the clinical and nutritional status will be measured. Each patient's nutritional needs will be calculated individually. The statistical analysis would be based on the intention to treat. Ethics and dissemination: The vice-chancellor of the research centre of Mashhad University of Medical Sciences is sponsoring this study. IR.MUMS.MEDICAL.REC.1400.113. Trial registration number: Iranian Registry of Clinical Trials (IRCT) Id: IRCT20210508051223N1, Registration date: 26 July 2021.